Pulse-based cropping systems for soil health restoration, resources conservation, and nutritional and environmental security in rainfed agroecosystems - Kumar, Sandeep; Gopinath, K. A.; Sheoran, Seema; Meena, Ram Swaroop; Srinivasarao, Ch.; Bedwal, Sandeep; Jangir, Chetan Kumar; Mrunalini, Kancheti; Jat, Ramdhan; Praharaj, C. S. (Frontiers in Microbiology, 2023)
Pulses are an important source of energy and protein, essential amino acids, dietary fibers, minerals, and vitamins, and play a significant role in addressing global nutritional security. The global pulse area, production, and average productivity increased from 1961 to 2020 (60 years). Pulses are usually grown under rainfed, highly unstable, and complex production environments, with substantial variability in soil and environmental factors, high year-to-year output variability, and variation in soil moisture. Since the last six decades, there is not much satisfactory improvement in the yield of pulses because of their cultivation in harsh environments, coupled with their continuous ignorance of the farmers and governments in policy planning. As a result, the global food supplies through pulses remained negligible and amounted to merely ~1.0% of the total food supply and 1.2% of the vegan food system. In this situation, protein-rich food is still a question raised at the global level to make a malnutrition-free world. Pulses are a vital component of agricultural biological diversity, essential for tackling climate change, and serve as an energy diet for vegetarians. Pulses can mitigate climate change by reducing the dependence on synthetic fertilizers that artificially introduce nitrogen (N) into the soil. The high demand and manufacture of chemical fertilizers emit greenhouse gases (GHGs), and their overuse can harm the environment. In addition, the increasing demand for the vegetal protein under most global agroecosystems has to be met with under a stressed rainfed situation. The rainfed agroecosystem is a shelter for poor people from a significant part of the globe, such as Africa, South Asia, and Latin America. Nearly, 83% [over 1,260 million hectares (ha)] of cultivated land comes under rainfed agriculture, contributing significantly to global food security by supplying over 60% of the food. In rainfed areas, the limitation of natural resources with the shrinking land, continuous nutrient mining, soil fertility depletion, declining productivity factor, constantly depleting water availability, decreasing soil carbon (C) stock, augmented weed menace, ecological instability, and reduced system productivity are creating a more challenging situation. Pulses, being crops of marginal and semi-marginal soils of arid and semi-arid climates, require less input for cultivation, such as water, nutrients, tillage, labor, and energy. Furthermore, accommodation of the area for the cultivation of pulses reduces the groundwater exploitation, C and N footprints, agrochemical application in the cropping systems, and ill effects of climate change due to their inherent capacity to withstand harsh soil to exhibit phytoremediation properties and to stand well under stressed environmental condition. This article focuses on the role of pulses in ecological services, human wellbeing, soil, environmental health, and economic security for advanced sustainability. Therefore, this study will enhance the understanding of productivity improvement in a system-based approach in a rainfed agroecosystem through the involvement of pulses. Furthermore, the present study highlighted significant research findings and policy support in the direction of exploring the real yield potential of pulses. It will provide a road map to producers, researchers, policymakers, and government planners working on pulses to promote them in rainfed agroecosystems to achieve the United Nations (UN's) Sustainable Development Goals (SDGs).